Competing theories of growth models and their forecast ability of actual output growth - Netshipale, Dembe (My University, 2021)
This dissertation examines correlation between real output growth and projected output growth for diverse schools of thought. In this research study, we measure projected output growth of Australia, Brazil, France, Germany, South Korea, South Africa (S.A.), the United Kingdom (U.K.) and the United States (U.S.), using the Domar model, Solow model, extended Solow model, Goodwin’s model, AK model, Lucas model and Romer model for the period from 1970 to 2017, then compare it to the actual output values to see if there exist a co - movement between the two variables and the correlation. We use both the ordinary least squares (OLS) regression and root mean square error (RMSE) to compare the performance of projected output growth for the above-mentioned period. The OLS results show that the Solow model, the extended Solow model, Goodwin’s model, and Lucas model the impact of projected output growth on real output growth is positive for all the countries and statistically significant. For the Domar model, the parameter term is significant, and the model predicts a positive impact on projected output growth, except for SA. We also present the graphic representation of real output growth and projected output growth for seven growth models. The results show a strong co-movement between real output growth and projected output growth for extended Solow, Solow and Domar model. The RMSE estimate of real output growth and projected output growth for Solow model and extended Solow model provides superior estimate ability. Lastly, we use in-sample and out-of-sample forecasts, by utilizing RMSE, to determine which model possess the most superior forecasting ability for the one year, two year and three year time horizon. The in-sample results illustrate that, generally, the Goodwin model outperforms other models followed by extended Solow model then The AK and Lucas models. The out-of-sample results yield the following results: The extended Solow model generally outperforms the other models, followed by Solow model then Domar and Lucas models.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Economic Science) to the Faculty of Commerce, Law and Management, School of Economic and Business Sciences, University of the Witwatersrand, Johannesburg, 2021